The Baltics : Medium-Term Fiscal Issues Related to EU and NATO Accession. (IMF Staff Country Reports; Country Report, 2002)
This paper on the Baltic countries analyzes medium-term fiscal issues related to European Union (EU) and NATO accession. The paper supports the Baltic authorities' intention to aim at balancing their budgets over the economic cycle. The paper describes the Baltics' current fiscal position and structure. It reviews theory and empirical evidence of the possible macroeconomic benefits of fiscal adjustment. It also reviews the experience of earlier EU accession countries prior to and after their accession. The medium-term fiscal frameworks are also presented.